1978
DOI: 10.1007/bf01401631
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure and pressure volume relation in patients with subarachnoid haemorrhage (SAH)

Abstract: The development of the intracranial pressure after a subarachnoid haemorrhage was evaluated in 21 patients. A statistically significant relation between the intracranial pressure and the neurological findings was found, whereas vasospasms did not influence the intracranial pressure. In patients in a clinically critical condition, rhythmic pressure waves of a frequency of 1/minute were repeatedly observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 13 publications
(17 reference statements)
2
4
1
1
Order By: Relevance
“…In the intensive care setting a significant correlation between ICP and H&H grades has been described in patients with SAH. [13][14][15][16] This finding is in agreement with the result of the current study in which a significant correlation between H&H grade and ICP before 13 In a recent study lumbar cerebrospinal fluid pressure was measured in patients subjected to craniotomy in the supine position. A decrease in ICP averaging 1.8 mmHg was found with 30º of head-up position, whereas CPP and MABP did not change significantly.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the intensive care setting a significant correlation between ICP and H&H grades has been described in patients with SAH. [13][14][15][16] This finding is in agreement with the result of the current study in which a significant correlation between H&H grade and ICP before 13 In a recent study lumbar cerebrospinal fluid pressure was measured in patients subjected to craniotomy in the supine position. A decrease in ICP averaging 1.8 mmHg was found with 30º of head-up position, whereas CPP and MABP did not change significantly.…”
Section: Discussionsupporting
confidence: 94%
“…12 In patients with cerebral aneurysms a significant association between ICP and Hunt & Hess (H&H) gradation has been demonstrated in the intensive care setting. [13][14][15][16] However, in 1 perioperative study this relationship was not found. 17 Recently, we found that in patients with space-occupying lesions cerebral swelling occurs with a 5% probability at ICP less than 5 mmHg and a 95% probability at ICP more than 13 mmHg.…”
contrasting
confidence: 56%
“…The growth of brain edema volume and the depletion of CSS volume buffering capacity observed during the 3-5-day post trauma period, confirm data gathered on brain edema dynamics by several other authors using other methods (Kobrine and Kempe 1973;Hase et al 1978;Auer 1979;Reulen et al 1980;Cao et al 1984). …”
Section: Discussionsupporting
confidence: 88%
“…42 Studies have demonstrated that when ICP is unresponsive to medical therapy, there is an increase in poor outcome. [43][44][45][46][47][48][49] Recent literature has begun to question the practice variation in ICP monitoring, 50,51 and the optimal target for interventions aimed to treat ICP. 52…”
Section: Intracranial Pressurementioning
confidence: 99%